Morphology Changing at Incipient Crystallization Condition. (8th April 2015) - Toshima, Takeshi; Hamai, Ryo; Fujita, Saya; Takemura, Yuka; Takamatsu, Saori; Tafu, Masamoto
Abstract: Brushite (Dicalcium phosphate dihydrate, (DCPD), CaHPO4 ·2H2 O) is one of key components in calcium phosphate system due to wide attractive material not only as bioceramics but also environmental materials. Morphology of DCPD crystals is important factor when one uses its functionality with chemical reaction; because its surface crystal face, shape and size rule the chemical reactivity, responsiveness. Moreover, physical properties are also changed the morphology; such as cohesion, dispersiveness, permeability and so on. If one uses DCPD crystals as environmental renovation materials to catch the fluoride ions, their shape require 020 crystal surfaces; which usually restricts their shape as plate-like structure. After the chemical reaction, the shape of sludge is not good for handling due to their agglutinate property. Therefore searching an effective parameter and developing the method to control the morphology of DCPD crystals is required. In past, we reported that initial concentration and pH value of starting solution, prepared by dissolving calcium nitrate, Ca(NO3 )2 and ammonium dihydrogen phosphate, NH4 H2 PO4, changes the morphology of DCPD crystals and phase diagram of morphology of DCPD crystal depend on those parameter. The DCPD crystallization shows unique behaviour; products obtained higher initial concentration form single crystal-like structure and under lower condition, they form agglomerate crystal-like structure. These results contradict usual crystallization. Here we report that the effect of mixing process of two solutions. The morphology of DCPD crystals is changed from plate structure to petal structure by the arrangement. Our result suggests that morphology of DCPD crystals strongly depends at incipient crystallization condition and growth form is controllable by setting initial crystallization condition.